Wetlands and wellbeing: Balancing the needs for conservation and livelihoods - Amerasinghe, Priyanie; Marambanyika, Thomas; Wickramaratne, Chaturangi; McCartney, Matthew P. (CGIAR, 2024)
Wetlands, through the provision of a range of direct and indirect ecosystem services, play a vital role in supporting and sustaining peoples’ livelihoods, health, and wellbeing. Yet over the past three centuries, almost 90 percent of these critically important ecosystems have been degraded. The theme of this year’s World Wetlands Day is Wetlands and Human Wellbeing, and in this NEXUS Gains Talk, we explore the theme through case studies from Asia and Africa, with input from Ramsar.